2001 Physics Education Research Conference Proceedings 2001
DOI: 10.1119/perc.2001.pr.006
|View full text |Cite
|
Sign up to set email alerts
|

Instructors’ Ideas about Problem Solving – Setting Goals

Abstract: This paper presents preliminary hypotheses about the relationship between faculty goals for the introductory calculus-based physics course and their beliefs about student learning of problem solving. All faculty have problem solving as a major goal for their course. There appears to be however, an instructional paradox. When discussing how students learn to solve problems in their own courses, faculty indicate that reflective-practice skills are a necessary prerequisite, and that average students enter the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Similar to other studies [2], all described their primary instructional goals as developing students' understanding of physics principles and ability to solve problems related to these principles. None of the instructors felt their students were fully achieving these goals, with three expressing the belief that many of their students were falling far short.…”
Section: Instructional Goalsmentioning
confidence: 95%
“…Similar to other studies [2], all described their primary instructional goals as developing students' understanding of physics principles and ability to solve problems related to these principles. None of the instructors felt their students were fully achieving these goals, with three expressing the belief that many of their students were falling far short.…”
Section: Instructional Goalsmentioning
confidence: 95%
“…Problem solving is viewed as a fundamental part of learning science in regular schools (Reif et al, 1976;Larkin & Reif, 1979;Chi et al, 1981;Reif, 1981;Bascones et al, 1985;Amigues, 1988;Robertson, 1990;Savage & Williams, 1990;McDermott, 1991;Henderson et al, 2001;Kuo, 2004;Pol, 2005;Yerushalmi & Magen, 2006;Loucks, 2007). After the instructor introduces the concepts, students apply these concepts in problems.…”
Section: The Definition Of Problem Solvingmentioning
confidence: 99%
“…These are experimental/statistical research (four studies), case study (one study), individual interview (one study), and protocol analysis (seven studies). With the exception of one study that used statistical measurement (Bascones et al, 1985) and two that used interviews (Henderson et al, 2001;Kuo, 2004), most of the studies produced thinking aloud protocols (Simon & Simon, 1978;Larkin & Reif, 1979;Larkin et al, 1980;Chi et al, 1981;Larkin, 1981;Amigues, 1988;Robertson, 1990). Also it was reported that those metacognitive behaviours improved with thinking-aloud protocols which could also be a suitable method for physics problemsolving (Anderson & Nashon, 2006;Meijer et al, 2006).…”
Section: Metacognition In Problem Solvingmentioning
confidence: 99%
“…As a result, many students are able to answer physics questions correctly but do not know the physics concepts related to the questions. (Henderson, Heller, Heller, Kuo, & Yerushalmi, 2001). Besides, the multiple choice test does not consist of many information because it only raises the final answer of the students (Kastner & Stang, 2011).…”
Section: Introductionmentioning
confidence: 99%